Economic Development and CO2 Emissions: A Nonparametric Panel Approach - Théophile Azomahou; François Laisney; Nguyen van Phu (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2005)
We examine the empirical relation between CO2 emissions per capita and GDP per capita during the period 1960-1996, using a panel of 100 countries. Relying on the nonparametric poolability test of Baltagi et al. (1996), we find evidence of structural stability of the relationship. We then specify a nonparametric panel data model with country-specific effects. Estimation results show that this relationship is upward sloping. Nonparametric specification tests do not reject monotonicity but do reject the polynomial functional form which leads to the environmental Kuznets curve in several studies.
Keywords: O40; C23; C14; O10; 330; Environmental Kuznets curve; panel data; poolability test; mono- tonicity test; specification test; Environmental Kuznets Curve; Luftverunreinigung; Kohlendioxid; Sozialprodukt; Schätzung